Clinical Features of Respiratory Syncytial Virus Infection in Neonates: A Single Center Study - Sung Hui Chang; Gwang Cheon Jang; Shin Won Yoon (Korean Society of Neonatology, 2018)
Purpose The aim of this study was to investigate the clinical characteristics of Respiratory syncytial virus (RSV) infection during the neonatal period to provide information that is useful in clinical practice and suggest extension of the palivizumab administration. Methods Neonates admitted to the National Health Insurance Service Ilsan Hospital neonatal intensive care unit due to respiratory symptoms and for whom multiplex reverse transcription-polymerase chain reaction and multiplex real time-polymerase chain reaction tests were performed between October 2011 and May 2016 were included in this study. Medical records were retrospectively reviewed, and data was collected for 156 neonates. Results Among the 156 neonates, RSV was detected in 114 (73.1%), non-RSV in 25 (16%), and no virus in 17 (10.9%). The majority were full term infants (92.4%) and peak incidence of RSV infection was in January. Post-natal care center infection was more common in the RSV group (46.6%) than that in the other virus groups (24%, P=0.0243). Clinical symptoms were severe in the RSV group in contrast to that in the non-RSV or others groups. The RSV group frequently needed oxygen therapy (P=0.0001) and the duration of hospital stays were longer (P=0.0001). Conclusion RSV is a significant cause of respiratory infection in neonates and the severity is higher in contrast to that with other viral causes of infection. Infants in post-natal care centers have a high-risk of developing RSV infections; therefore, palivizumab administration may be considered in this group to prevent hospitalization and reduce the duration of hospital stay.